Exploring Agroecological Sustainability: Unearthing Innovators and Documenting a Community of Practice in Southeast Australia. Issue 5 (4th May 2017) - Cross, Rebecca; Ampt, Peter
ABSTRACT: In this article we describe a movement to regenerate and sustainably use native grasslands using innovative grazing and cropping strategies. We find that this movement has the essential characteristics of a "community of practice" (COP) and is a strong example of a bottom-up transition toward a sustainable agroecological farming system. This COP was identified and described using participatory rural appraisals followed by biophysical and sociocultural studies with active COP members. Using these multiple mixed-method approaches helped characterize the COP's many layers, revealing how and why it is driven and fashioned by innovators who collaborate via joint enterprise, mutual engagement, and shared repertoire. Holistic Management, Grazing for Profit, and Stipa Native Grasses Association were the key enabling programs/associations for the COP, which, like other agroecological movements, exists on the margins of conventional agri-innovation systems and endures with little public acknowledgment or support. It is a potent grass-roots example of adaptive farm management that generates optimism in the farming families involved, and challenges existing research and extension paradigms regarding both innovation and practice change.